The Role of the Principal of SD Nur Ihsan in the Education Supervisor - Ahmad Ardhi Mauluddin Sitorus; Bunga Br Lubis; Lydia Amelia; Suhada Aulia Fahra Harahap; Yusnia Meha; Yusril Ardiansyah; Inom Nasution (Edumaspul: Jurnal Pendidikan, 2022)
The principal in his position as a supervisor is obliged to foster teachers to become good educators and teachers. For teachers who are good, the quality can be maintained and for teachers who are not good, it can be developed to be better. Meanwhile, all good and competent teachers as well as those who are still weak must be sought so that they are not outdated in the learning process and the materials used as teaching materials. The principal as a supervisor must be realized in the ability to compose and implement educational supervision programs and take advantage of the results. In order for the implementation of these tasks to be carried out properly, the principal is required to have various methods and techniques of supervision, especially those relating to the implementation of the duties of teachers and employees, and job growth. Because the principal as the main leader and mover in the implementation of education and learning. Therefore, the principal has a very important role in the supervision of education. On that basis, this research is addressed to the principal. The research method is used with qualitative methods and also a descriptive approach. The study used interviews regarding the role in educational supervision.